Nonconductiong poly(o-aminophenol) films in the field of the bioelectrochemistry - Tucceri, Ismael Ricardo (2013)
The practical use of non-conducting poly(o-aminophenol) (POAP) films in the field of the bioelectrochemistry is discussed in this paper. Particular emphasis is given to the effects of applied potential, solution pH and interferents on the response current of biosensors based on POAP.